1998
DOI: 10.2176/nmc.38.566
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Disease Associated With Pulmonary Sarcoidosis —Case Report—

Abstract: A 61-year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…There was no angiographic evidence of vasculitis, and evidence of meningitis was not present on CSF examination. Moreover, autopsy fi ndings of the case mentioned above [3] showed marked fi brous intimal thickening in the bilateral ICAs but without active infl ammation [3] . Therefore, moyamoya-like vascular abnormality associated with sarcoidosis may not be related to active infl ammation.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…There was no angiographic evidence of vasculitis, and evidence of meningitis was not present on CSF examination. Moreover, autopsy fi ndings of the case mentioned above [3] showed marked fi brous intimal thickening in the bilateral ICAs but without active infl ammation [3] . Therefore, moyamoya-like vascular abnormality associated with sarcoidosis may not be related to active infl ammation.…”
Section: Discussionmentioning
confidence: 95%
“…Another study reported segmental narrowing and dilatation of large cerebral arteries [7] , but clinical correlation was not made. To our knowledge, there has been only one reported patient who had moyamoya-like vasculopathy associated with sarcoidosis [3] . Similar to our case, the patient had bilat- eral ICA occlusion at the terminal portion.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations